Youth Employment Issues and their Impact on the Economic Development of Nepal - Sharma, Laxmi Kanta; Paudel, Vishal (Journal of Development and Administrative Studies, 2023)
Youth unemployment in Nepal is a significant and persistent challenge, posing serious threats to the country’s economic development and social stability. This study investigates the causes, impacts, and potential solutions to youth unemployment, specifically focusing on Kathmandu Valley. Employing qualitative methods such as interviews, focus groups, and document analysis, the research captures perspectives from unemployed youth, employers, educators, policymakers, and NGO representatives. The findings reveal a stark disconnect between the education system and labor market needs, exacerbated by outdated curricula and inadequate vocational training. Economic stagnation, societal biases favoring white-collar jobs, and insufficient support for entrepreneurship further compound the issue. The consequences of youth unemployment are extensive, ranging from lost productivity and skills erosion to financial dependency and mental health challenges among young people. The study emphasizes the urgent need for education reform, the expansion of vocational training, and the creation of policies that foster entrepreneurship and align workforce skills with market demands. By addressing these systemic barriers, Nepal can harness its youthful population as a transformative force for sustainable economic growth and social progress.